The Influence of Product Attributes and Customer Experience on Customer Loyalty : (Study on Café Customers in Malang City) - Syech M A Zain Al Amrie; Rohmat Dwi Jatmiko; Eko Handayanto (Universitas Muhammadiyah Malang, 2021)
This study describes loyalty, product attributes, and customer experience at 5 cafes in Malang City and analyzes the influence of product attributes and customer experience on customer loyalty. The research sample is cafe customers totaling 150 people with purposive sampling technique. Analysis of the data used to determine the level of loyalty, product attributes, and customer experience is a scale range analysis. Multiple linear regression analysis was used to determine the influence of product attributes and customer experience on customer loyalty. The results of the scale range indicate that cafe customers are loyal, product attributes are appropriate and customer experience tends to be positive and pleasant. The results of multiple linear regression analysis show that product attributes and customer experience significantly influence customer loyalty either simultaneously or partially.